Efektivitas media papan bangun datar dalam meningkatkan pemahaman konsep geometri pada siswa kelas 4 di SDI Surya Buana - Maharani, Naura Qur’atin (Maliki Interdisciplinary Journal, 2024)
Basic mathematics learning usually shows a tendency for teachers to use media that is less than optimal, the media used is very simple and does not attract students’ attention. Innovative media are ideas, practices, or objects that are considered new media, including flat boards. This research aims to obtain information regarding: 1) the application of innovative media; 2) the role of media (innovative); and 3) the impact of applying innovative media in mathematics learning. In qualitative research, two studies were conducted to assess students on the application of PGMI innovative media in elementary school mathematics learning. The subjects in this research included 23 fourth grade students at Surya Buana Islamic Elementary School, Malang. Technical data collection uses documentation, observation and interview techniques. There is a need for innovative media at the elaboration stage (concept explanation) as confirmation of core activities. And the impact of implementing innovative media for teachers and students is increasing teacher’s abilities in holding and using media, managing learning time effectively; and improve student learning outcomes.